Crosstalk Between the Autophagy-Lysosome Pathway and the Ubiquitin-Proteasome Pathway in Retinal Pigment Epithelial Cells - Zhan, J.; He, J.; Zhou, Y.; Wu, M.; Liu, Y.; Shang, F.; Zhang, X. (Current Molecular Medicine, 2016)
Background: The accumulation of damaged or misfolded proteins in retinal pigment epithelial (RPE) cells was considered a contributing factor for RPE dysfunction in age-related macular degeneration (AMD). The ubiquitinproteasome pathway (UPP) and the autophagy-lysosome pathway (ALP) are the two major proteolytic systems for clearance of misfolded or damaged proteins. Objective: The aim is to investigate how these two systems communicate and coordinate with each other in RPE cells for eliminating intracellular misfolded and damaged proteins. Methods: Cultured ARPE-19 cells were treated with proteasome inhibitor MG132 and lysosomotropic agent chloroquine (CQ), respectively. The levels and cellular distributions of ubiquitinated proteins, LC3-I, LC3-II, LAMP1 and p62 were analyzed by Western blotting and immunofluorescence. Proteasome activity was determined using Suc-LLVY-AMC as a substrate. Results: The level of ubiquitinated protein aggregations was significantly increased after the treatment of MG132 in RPE cells. The levels of LC3-I, LC3-II and LAMP1 increased in MG132 treated cells. The levels of γ-tubulin and p62 also increased in MG132 treated cells, suggesting that inhibition of the UPP up-regulates autophagy-lysosome pathway. Inhibition of lysosomal activity with CQ also increased the levels of high mass ubiquitin conjugates, LC3-II and p62. In addition, proteasome activity was compromised upon prolonged lysosomal inhibition. Conclusions: These data indicate that the UPP and the ALP are interrelated and that dysfunction of the ALP would also result in dysfunction of the UPP and severely compromise the capacity of eliminating misfolded and other forms of damaged proteins.
Keywords: lysosome